Wiedza w sieciowych korporacjach - Galant, Violetta (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The network corporation is a relatively new organization form. The knowledge as an asset plays a special role in the organizational entities as well as in the whole network corporation. This asset needs a new management method. Also this process should be preceded by a preparatory level - the knowledge location. People, their artifacts as well as organizational entities create the knowledge reservoirs of the network corporation. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1086, s. 131-141